The Sequence and Three-Dimensional Structure Characterization of Snake Venom Phospholipases B - Ullah, Anwar; Masood, Rehana (Frontiers in Molecular Biosciences, 2020)
Snake venom phospholipases B (SVPLBs) are the least studied enzymes. They constitute about 1%of Bothrops crude venoms, however; in other snake venoms, it is present in less than 1%. These enzymes are considered the most potent hemolytic agent in the venom. Currently, no structural information is available about these enzymes from snake venom. To better understand its threedimensional structure and mechanisms of envenomation, the current work describes the first model-based structure report of this enzyme from Bothrops moojeni (B. moojeni) venom named as B.moojeni phospholipase B (PLB_Bm). The structure model of PLB_Bm was generated using model building software like I-TESSER, MODELLER 9v19, and Swiss-Model. The build PLB_Bm model was validated using validation tools (PROCHECK, ERRAT, Molecular Dynamic Simulation, and Verif3D). The analysis of the PLB_Bm modeled structure indicates that its three-dimensional structure contains 491 amino acid residues that fold into a well-defined four-layer αββα sandwich core and has a typical fold of the N-terminal nucleophile aminohydrolase (Ntn-hydrolases). The overall structure of PLB_Bm contains eighteen beta strands and seventeen alpha-helices with many connecting loops. The structure divides into two chains (A and B) after maturation. The A chain is small and contains 207 amino acid residues while the B chain is large and contains 266 amino acid